C1-continuous time integration based on cubic Hermite interpolation - Mergel, J.C.; Sauer, R.A.; Ober-Blöbaum, Sina (PAMM)

Time transformed mixed integer optimal control problems with impacts - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

Higher order variational integrators in optimal control theory - Ober-Blöbaum, Sina (PAMM)

Variational multirate integration in multi-body dynamics - Gail, T.; Leyendecker, S.; Ober-Blöbaum, S. (PAMM)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
In this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
n this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, Kathrin (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, Maik; Ober-Blöbaum, Sina; Leyendecker, Sigrid (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (Proceedings of Applied Mathematics and Mechanics)

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, K. (PAMM)

Adaptive FEM with goal-oriented error estimation and an approximation of the dual problem for inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Uncertainty quantification for linear elastic bodies with two fluctuating input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

A coupled phase-field - Cahn-Hilliard model for lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Transition from hyperelastic micromorphic to micropolar and microstrain continua - Leismann, Thorben; Mahnken, Rolf (PAMM)